1999
DOI: 10.1191/074823399678846673
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk reduction strategies for the management of agricultural nonpoint source pesticide runoff in estuarine ecosystems

Abstract: Agricultural nonpoint source (NPS) runoff may result in significant discharges of pesticides, suspended sediments, and fertilizers into estuarine habitats adjacent to agricultural areas or downstream from agricultural watersheds. Exposure of estuarine fin fish and shellfish to toxic levels of pesticides may occur, resulting in significant declines in field populations. Integrated pest management (IPM), best management practices (BMP), and retention ponds (RP) are risk management tools that have been proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…A parallel study using laboratory testing with amphipod (Hyalella azteca) indicated that 44 m of vegetated and 111 m of nonvegetated wetland would reduce the mortality to \5% (Schulz et al 2003c). The implementation of retention ponds in agricultural watersheds was examined by Scott et al (1999) as one strategy to reduce the amount and toxicity of runoffrelated insecticide pollution discharging into estuaries. However, wetland sizes and retention rates are not further detailed.…”
Section: Relevant Biological Endpointsmentioning
confidence: 99%
“…A parallel study using laboratory testing with amphipod (Hyalella azteca) indicated that 44 m of vegetated and 111 m of nonvegetated wetland would reduce the mortality to \5% (Schulz et al 2003c). The implementation of retention ponds in agricultural watersheds was examined by Scott et al (1999) as one strategy to reduce the amount and toxicity of runoffrelated insecticide pollution discharging into estuaries. However, wetland sizes and retention rates are not further detailed.…”
Section: Relevant Biological Endpointsmentioning
confidence: 99%
“…Additionally, alteration of the landscape often increases rates of sedimentation (Crossland et al, 2005;Syvitski et al, 2005;Syvitski and Milliman, 2007) that can smother sessile species or reduce their viability by altering light levels. Agricultural activities and sewage effluent lead to eutrophication in these systems (Scott et al, 1999;Costanzo et al, 2001;Rabalais et al, 2009Rabalais et al, , 2010, and shoreline hardening and other physical alterations can disrupt coastal ecosystems (Rice, 2006;Jackson et al, 2008;Morley et al, 2012). All of these insults collectively alter and destroy biogenic habitats occurring in marine coastal regions (Duarte et al, 2008(Duarte et al, , 2013McLeod et al, 2011;Fourqurean et al, 2012;Watanabe and Kuwae, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the "sediment situation", many toxicants may not be bioavailable to meiofauna (Coull & Chandler, 1992) due to their toxicities may be reduced by several factors such as chelation, complexation, or by binding to organic ligands and colloidal aggregations on the sediment surface (Giere, 2009). On one hand, Scott et al (1999) determined a LC50 of 1.01 µg.L -1 for the estuarine grass shrimp Paleomonetes pugio by field and laboratory bioassays due to gravid female grass shrimp populations have elevated levels of P-glycoprotein (P-gp), a multidrug resistance protein, which may transport various pesticides across cellular membranes. On the other hand, Leonard et al (2001) determined a 10-d no observed effect using 42 µg.kg -1 sediment-associated endosulfan for the epibenthic mayfly Jappa kutera.…”
Section: Endosulfan Effects On Meiofauna Structurementioning
confidence: 99%